Family support groups for family members of mentally ill offenders : family expectations and experiences - Audenaert, Kurt (2018)
Family Support Groups (FSGs) are developed for family members of mentally ill offenders. This study investigates family treatment expectations and experiences of an FSG. Family members were interviewed before (n = 20) and after (n = 17) attending an FSG. Results show that family members hesitated or were curious about the FSG, expected to receive peer support and universality of problems, to receive information and advice and thought about the safety and respect of the group. Family members experienced the treatment as helpful because it was supportive, they gained new insights and they felt relieved and satisfied. Many family members see the guidance of the therapists and the differences in family and gender roles as an added value of attending an FSG. However, considering the limitations of the study, future studies should gain insight in and stress the importance of the meaning of therapeutic processes for family members confronted with different psychiatric disorders and/or situations